Climate Change Governance and Adaptation : Case Studies from South Asia - Barua, Anamika; Narain, Vishal; Vij, Sumit; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
Climate change in this book is seen not only as an environmental problem but as a societal challenge too and as such discusses the governance issues from an interdisciplinary approach and across different scales: local, state, and national. Drawing governance lessons from case studies across South Asia, the book addresses the impact of urbanization and migration, the role of financing mechanisms and the economics of adaptation, and emphasizes that a top down approach in governing climate change adaptation and mitigation may not provide desired outcomes. The authors use governance as a lens to understand the challenges and opportunities regarding climate adaptation and mitigation strategies.
1. Governance of Climate Change: Issues and Challenges in South Asia 2. "A Disappearing" or a Resilient Ganga? Climate Change Perspectives from the Himalaya 3. Deliberative Governance on Vulnerability to Climate Change: Voices from Madhesi Farmers 4. Waste or Savior? Two Cases of Emerging Wastewater Irrigation in Urbanizing Kathmandu Valley 5. Climate Migration and Flood Related Disasters 6. Changing Social Capital in the Mountains and the Implications for Adaptation Interventions: An Exploratory Analysis with Case Studies from the Hindu Kush Himalaya 7. Enhancing Adaptive Capacity through Education: A Case Study of Rural Mountain Communities, Sikkim, Eastern Himalaya India 8. Governing National Actions for Global Climate Change Stabilization: Examples from India 9. Bridges and Barriers for Governance of Water Resources in South AsiaInsights from Brahmaputra Basin in India
Includes bibliographical references and index.
Also available in print format.
Keywords: Climatic changes -- South Asia; Climatic changes -- India; Climatic changes -- Social aspects -- South Asia; Climatic changes -- Social aspects -- India; Conservation of natural resources -- South Asia; Conservation of natural resources -- India; Climatic changes; Climatic changes -- Social aspects; Conservation of natural resources; NATURE / Environmental Conservation & Protection; POLITICAL SCIENCE / Public Policy / City Planning & Urban Development; Adaptive governance; Migration, society, adaptation; Multi-level governance; Periurban water; Psychosocial well-being.; Urbanization; Electronic books